Does anal sphincter injury preclude subsequent vaginal delivery?. (March 2016) - Fitzpatrick, M.; Cassidy, M.; Barassaud, M.L.; Hehir, M.P.; Hanly, A.M.; O'Connell, P.R.; O'Herlihy, C.
Abstract: Objective: To assess continence and anal sphincter integrity during a subsequent pregnancy and delivery in women known to have a previous anal sphincter injury. Design: Prospective observational study. Setting: The National Maternity Hospital, Dublin, Ireland. Population: Antenatal patients with a documented obstetric anal sphincter injury at a previous delivery. Methods: Women underwent symptom scoring, endoanal ultrasound and manometry. Main outcome measures: Recommended and actual mode of delivery, continence scores and endoanal ultrasound findings after index delivery. Results: 557 women were studied. 293 (53%) had no symptoms of faecal incontinence, 189 (34%) had mild symptoms and 75 (13%) moderate or severe symptoms. 408 (73%) had an endoanal ultrasound. 383(94%) had a normal or small (<1 quadrant) defect in the internal anal sphincter and 390 (96%) had a scar or small (<1e quadrant) defect in the external anal sphincter. 393 (70%) delivered vaginally. 164 (30%) were delivered by caesarean section. 197/557 (35%) returned for follow-up. There was no significant change in continence following either vaginal or caesarean delivery. 20 (5.1%) women had a recognised second anal sphincter tear during vaginal delivery. Conclusions: The majority of women who sustain a third degree tear have minimal or no symptoms of faecal incontinence when assessed antenatally in a subsequent pregnancy. 70% go on to have a vaginal delivery, with little impact on faecal continence. These findings provide reassurance for patients and clinicians about the safety of vaginal delivery following anal sphincter injury in appropriately selected patients.